Back to school: an analysis of repeat school victimization in Malmö. Issue 1 (2nd January 2022) - Johansson Worobiec, Magda
ABSTRACT: This study examines repeat school victimization, and is an extension of previous research. The distributions of two property crimes (burglary and theft) and three crimes against the person (assault, threats and harassment) in compulsory schools are compared between municipal and independent schools in Malmö, as well as between school areas with varying economic status. The time course between incidents is compared between crime types and between areas with low and high economic status, respectively. The study is based on reported crime data, and is geographically limited to the municipality of Malmö. The data relate to the period 2015–2017. The study's results show a skewed distribution for victimization in general, with municipal schools and schools in areas with low economic status being most affected. The majority of repeat school victimization takes place within a month of the previous incident, and this time frame applies to all four crime types. Burglaries and assaults are repeated more quickly in the most deprived areas, while for theft and threats/harassment, there is very little difference in the time course between different areas. Victimization differences and preventive implications are discussed based on the theories of routine activities, social disorganization and macro-level strain.